PENGARUH PERSEPSI KUALITAS PRODUK, DAYA TARIK PROMOSI, DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi Pembelian Produk Kosmetik Wardah Pada Mahasiswi FEB Universitas Diponegoro Semarang) - Yolanda, Rilla; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2017)
The purpose of this study was to analyze the influence of perception ofÂ product quality, attractiveness of promotions, and brand ambassador against purchasing decisions with the brand image as an intervening variable. This research was conducted to consumers who ever make a purchase in Wardah cosmetics, where the respondents in this study is the student of the Faculty of Economics and Business of the University of Diponegoro in the academic year of 2013-2016. The number of samples in this research as much as 131 respondents. With the method of collecting data through questionnaires and sampling method in this research is non probability sampling with purposive sampling technique. This research uses the Partial Least Square analysis techniques, which are being estimated by the program SmartPLS 2.0. A Summary of this research in that the perception ofÂ product quality, attractiveness of promotions, brand ambassador and brand image as an intervenning variable have an effect direcrly and indirectly against the purchasing decisions. Brand image is the factor that most affect consumers in makingÂ purchasing decisions. So the higher the brand image of a product then the higher the purchasing decisions of consumers on such products. The perceived benefits of greatly influence consumer purchase decisions in conducting at Wardah cosmetic products.